2003
DOI: 10.1021/ja035069w
|View full text |Cite
|
Sign up to set email alerts
|

Directed Self-Assembly of Two Kinds of Nanoparticles Utilizing Monolayer Films of Diblock Copolymer Micelles

Abstract: We demonstrated a self-assembly of two different kinds of nanoparticles simultaneously directed on a monolayer film of diblock copolymer micelles via physical and chemical arrangements. We first incorporated gold nanoparticles physically around the micelles of a monolayer film of PS-PVP micelles having a short-range hexagonal order. Iron oxide nanoparticles were then synthesized chemically in the PVP core area of the ordered micelles, resulting in a mosaic nanopattern of magnetic iron oxide nanoparticles surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
216
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(219 citation statements)
references
References 17 publications
2
216
0
1
Order By: Relevance
“…One approach is to directly evaporate or synthesize inorganic nanoparticles inside wellordered block polymer templates. Cohen, 85 Sohn, 86,87 Mö ller 88 and coworkers have shown that polymer/nanoparticle composites can be generated by directly reducing the metal precursors inside block copolymer templates of different morphologies. Jaeger and Lopes demonstrated that by evaporating a series of metal nanoparticles on polystyrene-block-poly(methyl methacrylate) templates, well-aligned metal wires could be obtained on the polystyrene domains after thermal treatment at 180 uC.…”
Section: Rod-type Nanoparticle Assembly At Fluid Interfacesmentioning
confidence: 99%
“…One approach is to directly evaporate or synthesize inorganic nanoparticles inside wellordered block polymer templates. Cohen, 85 Sohn, 86,87 Mö ller 88 and coworkers have shown that polymer/nanoparticle composites can be generated by directly reducing the metal precursors inside block copolymer templates of different morphologies. Jaeger and Lopes demonstrated that by evaporating a series of metal nanoparticles on polystyrene-block-poly(methyl methacrylate) templates, well-aligned metal wires could be obtained on the polystyrene domains after thermal treatment at 180 uC.…”
Section: Rod-type Nanoparticle Assembly At Fluid Interfacesmentioning
confidence: 99%
“…[1] In the last decade, significant progress in the synthesis of nanostructured materials with controlled size and morphology has been achieved. [2,3] One-, two-, or three-dimensional (1D, 2D, 3D) suprastructures assembled from preformed nanoparticles, [4] nanorods/wires and nanotube arrays, [5] nanostructured hollow spheres, [6] and mesostructured semiconductors have been successfully prepared. [7] In past research, amphiphilic molecules have usually been used either to direct nanoparticle aggregation or to form self-assemblies as templates for the fabrication of inorganic nanostructures.…”
mentioning
confidence: 99%
“…[63][64][65] Furthermore, block copolymer self-assembly provides the potential for the ordered assembly and stabilization of nanoscale metallic objects. 18,42,44,66,67 In what are often called nanoreactor approaches to polymer-nanoparticle composites, metals can be chelated to polymers in solution before self-assembly in bulk [Scheme 2(A)] or the bulk polymer film can be treated with metallic species after self-assembly [Scheme 2(B)]. In either case, nanoparticles are subsequently generated by a method appropriate to the metal species in the film, such as thermolysis, reduction, or exposure to plasma.…”
Section: Preparation Of Ligand-functional Block Co-mentioning
confidence: 99%
“…Although strategies for the organization of multicomponent systems have been carried out on micrometer length scales with the aid of microcontact printing 92 and on the nanometer scale by cocrystallization of nanoparticles of different sizes, 93 few examples of the organization of distinct chemical species on the nanometer scale through the specific localization of chemical functionality have appeared in the literature. One notable effort in this direction, carried out by Sohn et al, 66 allows the preparation of twodimensional arrays of both iron and gold nanoparticles by an oxygen plasma treatment of polymer films cast from solutions containing both gold nanoparticles and PS-PVP micelles with ferric trichloride coordinated to the pyridyl units in the micellar core.…”
Section: Toward the Arrangement Of Multiple Metalsmentioning
confidence: 99%